Efektivitas Model Pogil Ditinjau Dari Kemampuan Berpikir Kritis Matematis Siswa - Soraya, Rahayu; Mashari, Ali; Oktaviana, Evi (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2024)
The background of this research is the low level of students mathematical critical thinking skills. The aim of this research is to determine the effectiveness of the POGIL model in terms of students mathematical critical thinking skills. The population in this study were students of IV students and it consist of 3 classes. The sample for this research was students in classes IVA and IVB, selected using a purposive random sampling technique. This research is quasi-experimental research. This research uses a pretest-posttest control group design. The data in this research is data on students mathematical critical thinking skills in the form of quantitative data obtained from the pretest and posttest. Based on the results and discussion, it can be concluded that the POGIL model is effective in terms of students mathematical critical thinking skills.